2022
DOI: 10.1590/fst.24221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different stevia-to-onion ratios and heating temperatures on physicochemical and sensory attributes of onion-stevia hot water extracts

Abstract: Increased consumption of artificial and intense natural sweeteners have led to serious health implications and safety issues for intended consumers. Among all natural sweeteners, steviol glycosides (SGs: stevioside & rebaudioside-A) are popularly known as zero-caloric intense sweetening compounds of natural origin. Hot water extraction (HWE) is considered ecofriendly and less expensive, and HWE extracts are safe for human consumption as compared to organic solvents extraction. Onion (Allium cepa L.) and stevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Based on our previous study, OSHE was prepared by the following process as per the reported method of Yang et al ( 2021 ). Onion and stevia (onion:stevia ratio = 100:1, w/w) were heated at 115°C, for 4 h, at a pressure of 1.2 kgf/cm 2 , using a retort (STERI‐ACE PRS‐60‐1, Kyunghan Co., Ltd, Gyeongsan, South Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous study, OSHE was prepared by the following process as per the reported method of Yang et al ( 2021 ). Onion and stevia (onion:stevia ratio = 100:1, w/w) were heated at 115°C, for 4 h, at a pressure of 1.2 kgf/cm 2 , using a retort (STERI‐ACE PRS‐60‐1, Kyunghan Co., Ltd, Gyeongsan, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Onion comprises of moisture (ranging from 88.6% to 92.8%), fat trace (0.2%), ash (0.6%), and carbohydrates (ranging from 5.2% to 9.1%) (Bogevska et al, 2016 ; Griffiths et al, 2002 ; Jiang et al, 2021 ). The majority of the compositional framework of onion comprises dry matter content having nonstructural carbohydrates, such as fructans, sucrose, fructose, and glucose (Li et al, 2020 ; Yang et al, 2021 ). The sugar content of onion is subjected to variability during storage depending on storage temperature, postharvest treatments, and cultivar type.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are exacerbating factors in cellular injury and aging processes. In foods, ROS can cause lipid peroxidation, which leads to the deterioration of the foodstuffs (Li et al, 2020 ; Yang et al, 2021 ). The oxidative deterioration of lipid‐containing foods is responsible for the rancid odors and flavors during processing and storage, consequently decreasing the nutritional quality and safety of foods due to the formation of potentially toxic secondary compounds.…”
Section: Introductionmentioning
confidence: 99%